2016
DOI: 10.1071/rd14382
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the leptin receptor gene associated with delayed onset of puberty are also associated with decreased ovulation and lambing rates in prolific Davisdale sheep

Abstract: The aim of this study was to determine if single nucleotide polymorphisms (SNPs) in the leptin receptor (LEPR) gene associated with delayed onset of puberty are associated with changes in other reproductive traits in adult ewes. The ovulation rate of ewes homozygous for the SNPs was ~15% lower (PPLEPR SNPs than their wild-type or heterozygous contemporaries. Partial failure of multiple ovulations was also increased (PLEPR had on average 0.2 fewer lambs at mid-pregnancy and at birth compared with the wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In our study, LEPR gene was found as a candidate selection region (top 1% and 5% cut‐offs for F ST and Pi, respectively) on sheep chromosome 1. Previous studies have shown that the genetic mutations of LEPR are associated with fatness and reproductive traits such as ovulation rate, age at onset of puberty and also embryo attachment mechanisms during pregnancy (Fu, Li, Li, Fang, & Ren, ; Haldar at al., ; Juengel et al, ). Juengel et al () reported that the ewes homozygous for mutations in the LEPR gene have had ~15% ( p < 0.001) lower ovulation rate than their wild type in prolific Davisdale sheep.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, LEPR gene was found as a candidate selection region (top 1% and 5% cut‐offs for F ST and Pi, respectively) on sheep chromosome 1. Previous studies have shown that the genetic mutations of LEPR are associated with fatness and reproductive traits such as ovulation rate, age at onset of puberty and also embryo attachment mechanisms during pregnancy (Fu, Li, Li, Fang, & Ren, ; Haldar at al., ; Juengel et al, ). Juengel et al () reported that the ewes homozygous for mutations in the LEPR gene have had ~15% ( p < 0.001) lower ovulation rate than their wild type in prolific Davisdale sheep.…”
Section: Discussionmentioning
confidence: 97%
“…Substantial differences exist among breeds and numerous variations within breeds/sub-breeds. To date, the morphogenetic protein receptor type IB (BMPRIB) [1][2][3], bone morphogenetic protein 15 (BMP15) [4], growth differentiation factor 9 (GDF9) [5], beta-1,4-N-acetyl-galactosaminyl transferase 2 (B4GALNT2) [6], and leptin receptor (LEPR) [7] genes were considered as major candidate genes for prolificacy of sheep. It was determined that several sheep breeds with altered fecundity presented with >19 known variants in the BMPRIB (FecB B ), BMP15 (FecX B , FecX G , FecX H , FecX I , FecX L , FecX O , FecX R , FecX Bar , and FecX Gr ), GDF9 (FecG A , FecG E , FecG F , FecG H , FecG 1 , FecG T , and FecG V ), B4GALNT2 (FecL L ), and LEPR (FecD D ) genes ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The GDF9 mutations were observed in Cambridge and Cambridge (FecG H ) [5], Thoka (FecG T ) [18], Santa Ines (FecG E ) [19], Baluchi (FecG 1 ) [20], Norwegian White Sheep, Finn Ile de France sheep and Belclare (FecG F ) [21,22], Ile de France (FecG V ) [23], and Araucana creole sheep (FecG A ) [24]. The FecL L and FecD D mutations were seen in Lacaune [6] and Davisdale [7] sheep, respectively (Table 1). These mutations affecting ovulation rate and litter size have been well characterized in many different sheep populations globally, however, they might be present in as yet uncharacterized populations, and new mutations that are as yet described might also exist.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, ovulation rate and fetus survival are decisive managerial attributes. It has been well-documented that single-nucleotide polymorphism (SNP) in a narrow assembly of genes, including growth differentiation factor 9 (GDF9), bone morphogenetic protein 15 (BMP15), bone morphogenetic protein receptor 1 (BMPR1B), and leptin, can increase ovulation rate, multiple-lamb births, and fecundity in sheep (Souza et al, 2001;Wilson et al, 2001;Hanrahan et al, 2004;Juengel et al, 2004Juengel et al, , 2015. These genes belong to the transforming growth factor β (TGFβ) superfamily, which consists of 50 physiologically important macromolecules that regulate fertility and growth attributes, as well as cellular differentiation processes (Dong et al, 1996;Yan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%